Two-Year Follow-Up on Chemosensory Dysfunction and Adaptive Immune Response after Infection with SARS-CoV-2 in a Cohort of 44 Healthcare Workers - Sophia E. Schambeck; Laura M. Mateyka; Teresa Burrell; Natalia Graf; Ioana Brill; Thomas Stark; Ulrike Protzer; Dirk H. Busch; Markus Gerhard; Henriette Riehl; Holger Poppert (Life, 2022)
Persistent chemosensory dysfunction (PCD) is a common symptom of long-COVID. Chemosensory dysfunction (CD) as well as SARS-CoV-2-specific antibody levels and CD8+ T-cell immunity were investigated in a cohort of 44 healthcare workers up to a median of 721 days after a positive PCR test. CD was assessed using questionnaires and psychophysical screening tests. After 721 days, 11 of 44 (25%) participants reported PCD, with five describing an impaired quality of life. One participant reported hyperosmia (increased sense of smell). The risk of PCD at 721 days was higher for participants reporting qualitative changes (parosmia (altered smell), dysgeusia (altered taste), or phantosmia (hallucination of smell)) during initial infection than in those with isolated quantitative losses during the first COVID-19 infection (62.5% vs. 7.1%). The main recovery rate occurred within the first 100 days and did not continue until follow-up at 2 years. No correlation was found between antibody levels and CD, but we observed a trend of a higher percentage of T-cell responders in participants with CD. In conclusion, a significant proportion of patients suffer from PCD and impaired quality of life 2 years after initial infection. Qualitative changes in smell or taste during COVID-19 pose a higher risk for PCD.